Boat support and manufacturing method thereof
Through ball milling tank preparation, grouting molding, UV ozone treatment and high-temperature sintering, the iron content of traditional silicon carbide boat piles was successfully reduced, the problem of difficult to control the iron content was solved, and the preparation of low iron content and long-life silicon carbide boat piles was achieved, meeting the needs of the photovoltaic and semiconductor industries.
Patent Information
- Application Number
- CN202411607881.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The iron content of traditional reaction sintered silicon carbide boat carriers is difficult to control, resulting in silicon wafer pollution and short service life, which cannot meet the demand for pollution-free and long-life boat carriers in the photovoltaic and semiconductor industries.
The mud is prepared by a ball mill tank, and the blank of the boat holder splitting component is obtained through the grouting molding process, and the blank is carved by natural drying and hot air drying. Then, UV ozone treatment and high-temperature purification sintering. Finally, the iron content is reduced by high-temperature silicon permeability sintering and multiple process treatments, and a low-iron content silicon carbide boat holder is prepared.
It significantly reduces the iron content of the boat support, avoids silicon wafer pollution, extends the service life of the boat support, and meets the pollution-free and long-life boat support in the photovoltaic and semiconductor industries.
Smart Images

Figure BDA0005130109650000191 
Figure BDA0005130109650000201
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of boat support manufacturing, and in particular to a boat support and a manufacturing method thereof. Background Art
[0002] The boat support is a key bearing component of the diffusion process equipment in the photovoltaic and semiconductor industries. Its application in the photovoltaic and semiconductor industries is mainly in the production process of photovoltaic cells, as a carrier for photovoltaic cells. In the photovoltaic and semiconductor industries, the traditional boat support material is mainly quartz, but because the quartz boat support is easy to deform in high temperature environment and has a short service life of about 3-6 months, silicon carbide boat support, as a new type of boat support material, has gradually become the preferred boat support material in the photovoltaic and semiconductor industries due to its good thermal stability and long service life.
[0003] Silicon carbide has excellent high temperature resistance and corrosion resistance, and its strength is high. Due to the chemical properties of silicon carbide ceramics, it is difficult to form, so it is usually prepared by reaction sintering. The reaction sintering method includes the steps of powder preparation, block pressing, drying and sintering. These steps involve many parameters. For example, the powder preparation stage requires a reasonable ratio of raw materials and the preparation of powder with a compliant particle size. The block pressing stage requires reasonable pressure conditions and block size design, and the temperature setting and processing time setting of the drying and sintering stages. If these steps are not designed reasonably, it will affect the hardness and other indicators of the finished product.
[0004] Silicon carbide boat supports can replace quartz boat supports and have a longer service life of more than 5 years. The use of silicon carbide boat supports can significantly reduce the cost of use, reduce downtime caused by maintenance and repairs, and reduce production capacity losses. Silicon carbide, as the main raw material for making silicon carbide boat supports, has properties such as high strength, high elastic modulus, high thermal expansion coefficient, good thermal shock resistance and acid and alkali corrosion resistance. Due to these excellent properties, silicon carbide materials are often used in industrial fields such as microelectronics, mechanical seals, aerospace, and heat exchange. Silicon carbide micropowder, which is the raw material used to prepare silicon carbide ceramics, has a significant effect on the various properties of silicon carbide ceramics after sintering. In order to obtain silicon carbide ceramics with excellent performance, manufacturers have put forward strict requirements on the particle size, particle shape, purity and fluidity of silicon carbide powder.
[0005] The photovoltaic and semiconductor industries usually use quartz materials as boat supports to support the wafer boats. The wafer boats are loaded with silicon wafers for diffusion, coating and annealing processes. As the industry's requirements for the performance and efficiency of silicon wafers are becoming increasingly stringent, rapid thermal processing technology has been widely adopted, and increasingly stringent requirements have been placed on the kiln support. Quartz boat supports are rarely used, have a short lifespan and are easily damaged. They are gradually being replaced by silicon carbide boat supports with better performance. Although the bearing strength and lifespan of traditional reaction-sintered silicon carbide boat supports can meet industry requirements, their impurity content, especially the iron content, is difficult to control. A large number of applications have shown that the iron content in the reaction-sintered silicon carbide boat supports will contaminate the silicon wafers, causing the color of the silicon wafers to darken and become scrapped. Therefore, it is particularly important to find a boat support and a manufacturing method thereof. Summary of the invention
[0006] In order to solve the problems mentioned in the above background technology, the present invention provides a boat support and a manufacturing method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for manufacturing a boat support comprises the following steps:
[0009] S1. Prepare slurry by mixing raw materials, organic additives and pure water in a ball mill according to a certain proportion, and obtain a blank of the boat support split component by a slip injection molding process. After the blank is naturally dried and dried with hot air to remove moisture, it is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0010] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0011] The organic additive is a mixture of a binder, a dispersant and a defoamer;
[0012] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50-60min, and completing the ozone treatment to obtain a modified semi-finished product;
[0013] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000-2300° C. under the protection of inert gas, and obtaining a green blank of the silicon carbide boat support splitting component after high-temperature purification and sintering;
[0014] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650-1700℃. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning and drying processes to obtain a boat support with low iron content.
[0015] Preferably, the mass ratio of the raw material, the organic additive and pure water is (160-170):(6-8):(3-5).
[0016] Preferably, the green silicon carbide powder is mixed with green silicon carbide powder having three particle size distributions of average particle size of 90 to 100 μm, 8 to 10 μm and 1.5 to 2.5 μm;
[0017] The mass ratios of green silicon carbide powder with three particle size distributions to ultrapure carbon black are controlled within the range of [(30-35):(15-20):(47-50)]:(2-3).
[0018] Preferably, the method for high-temperature impurity removal treatment of the ultra-pure carbon black is: commercially available carbon black with a purity of ≥99% is sent into a vacuum furnace, and subjected to high-temperature impurity removal treatment at 1600 degrees under vacuum to obtain ultra-pure carbon black with a purity of ≥99.9%.
[0019] Preferably, the silicon used in the high-temperature siliconizing and sintering treatment is semiconductor silicon with a purity of 99.99% and a particle size of 3 to 5 mm. After the surface coating treatment, the semiconductor silicon is roasted together with the boat support that needs siliconizing treatment in a weight ratio of 15 to 30:100. The surface coating treatment is to add a slurry of ultra-pure carbon black, hexagonal boron nitride, PVP K90 and water during the heating and stirring of the semiconductor silicon, so that a layer of coating is coated on the surface of the silicon particles, a certain amount of moisture is quickly removed, and then it is slowly dried, and then forced to dry at 80°C before being put into the kiln to ensure that there is no moisture and the surface coating is intact.
[0020] Preferably, the impurity removal process uses dilute hydrochloric acid, the concentration is controlled at 8-15%, the temperature is controlled at 20-40° C., and the soaking time is controlled at 20-60 min.
[0021] Preferably, the organic additives are a binder, a dispersant and a defoamer mixed in a mass ratio of (3-5): (6-8): (1-2).
[0022] Preferably, the binder is OPTAPIXAC112;
[0023] The defoamer is CONTRASPUM KWE.
[0024] Preferably, the preparation method of the dispersant comprises the following steps:
[0025] S1. Mix graphene oxide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, diethylenetriamine, methylcellulose and polyethylene glycol uniformly and stand at 50-60° C. for 30-40 minutes to obtain a primary mixture;
[0026] S2. Add the primary mixture into a vacuum homogenizer for vacuum homogenization, control the vacuum degree during vacuum homogenization to be 0.1-0.3Mpa, the rotation speed to be 1500-2000rpm, and the homogenization time to be 30-60min;
[0027] S3. After homogenization, vacuum spray drying is performed, and the vacuum degree is controlled to be 0.3-0.5MPa, the atomization pressure is 0.5-0.8MPa, the air inlet temperature is 110-115°C, and the air outlet temperature is 45-55°C. After spray drying, the modified dispersant is obtained.
[0028] By adopting the above technical scheme, the prepared dispersant can be evenly dispersed in the organic additive, thereby improving the dispersing effect of green silicon carbide powder and ultra-pure carbon black in the organic additive, wherein the methyl cellulose that adsorbs polyethylene glycol to form a swollen body is stably dispersed in the system formed by the mixture B, and produces a synergistic effect with the viscosity system of the binder, thereby better improving the fluidity of the mud, so that the ball-milled mud has good grouting molding fluidity while also having good adhesion and formability, good viscosity stability and good forming stability, and reducing the generation of open pores, thereby ensuring the continuity of the heat conduction path of the boat support and the heat dissipation efficiency.
[0029] The equipment and tools such as mixers, ball mills, pressure grouting machines used in the processes of mud preparation, grouting molding, natural drying, etc. and the parts in contact with the mud are lined with non-metallic linings, which can be stainless steel and polyurethane linings, preferably polyurethane linings; the working environment is controlled at room temperature of 25°C to 35°C, relative humidity of 40% to 50%, and a closed dust-free workshop.
[0030] The hot air drying adopted uses an electric heating tube as the heat source. A heat circulation fan and pipeline are installed. A purification adsorber is installed at the pipeline inlet to purify dust, oil gas, water and other impurities in the circulating hot air.
[0031] The splicing uses mud to bond the parts together to form a complete boat support, and the required mud is mud used to make the product and is aged for more than 16 hours.
[0032] The high-temperature purification sintering adopts a medium-frequency graphite induction furnace. Before heating, first evacuate to a vacuum degree of less than 5Pa, start heating, add 3 to 4 hours at room temperature to 200℃, evacuate; add 4 to 6 hours at 201 to 900℃, stop evacuating, fill with high-purity nitrogen with a purity of 99.996% to restore normal pressure, start the wax exhaust fan to remove organic matter, and continue to fill with high-purity nitrogen at a rate of 30 to 50ml / min; heat at 900 to 1100℃ for 1 to 2 hours, evacuate; fill with high-purity argon with a purity of 99.996% at 1100 to 2000℃, sinter at normal pressure, and heat for 8 to 9 hours; heat at 2000 to 2300℃ for 8 to 9 hours; keep warm at 2300℃ for 5 hours. After high-temperature purification sintering, the obtained silicon carbide boat support split component blank has an open porosity of 8 to 10%, a strength greater than 100Mpa, and contains a small amount of free carbon.
[0033] The high-temperature siliconizing sintering adopts a vacuum graphite electrode furnace. Before heating, vacuum is first evacuated to a vacuum degree of less than 5Pa, and heating is started. The temperature is from room temperature to 200℃ for 1 to 2 hours, and vacuum is evacuated; the temperature is from 201 to 900℃ for 5 to 6 hours, and vacuum is stopped. High-purity nitrogen is filled to restore normal pressure, and the wax exhaust fan is started to remove organic matter, and high-purity nitrogen is continuously filled at a rate of 80 to 100 ml / min; the heating time is from 900 to 1100℃ for 1 to 2 hours, and vacuum is evacuated; the heating time is from 1100 to 1300℃ for 2 to 3 hours; the heating time is from 1300 to 1500℃ for 3 to 4 hours; the heating time is from 1500 to 1650℃ for 3 to 4 hours; and the temperature is kept at 1650℃ for 2 hours. High-purity nitrogen is filled when cooling down, and the temperature is naturally cooled down.
[0034] A boat support with low iron content manufactured by the above manufacturing method.
[0035] The product obtained after the above process is experimentally determined to have SiC% ≥ 95%, free silicon ≤ 5%, flexural strength ≥ 250Mpa, apparent porosity ≤ 0.01%, bulk density ≥ 3.02g / cm3, Fe content ≤ 5ppm, Ti content ≤ 5ppm, Mg content ≤ 3ppm, Zn content ≤ 2ppm, Al content ≤ 1ppm, Ca content ≤ 1ppm, and low impurity content, which can meet the requirements of silicon wafer diffusion process in photovoltaic and semiconductor industries for service life and pollution-free.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The low-iron-content pollution-free silicon carbide boat support manufactured according to the present invention can replace the quartz boat support in the photovoltaic and semiconductor industries. Because of its high compressive strength, excellent thermal conductivity and resistance to rapid cooling and heating, the service life of the boat support is greatly extended; at the same time, it overcomes the fatal weaknesses of traditional reaction-sintered silicon carbide, such as high iron content and serious pollution. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.
[0040] The high-temperature purification sintering adopts a medium-frequency graphite induction furnace. Before heating, the vacuum is first evacuated to a vacuum degree of less than 5Pa, and heating is started. The vacuum is evacuated at 100°C for 3 hours; the vacuum is evacuated at 500°C for 4 hours, and the vacuum is stopped. High-purity nitrogen with a purity of 99.996% is filled to restore normal pressure. At the same time, the wax exhaust fan is started to remove organic matter, and high-purity nitrogen is continuously filled at a rate of 30ml / min; the heating time is 900°C for 1 hour, and the vacuum is evacuated; the high-purity argon with a purity of 99.996% is filled at 1100°C, and the normal pressure sintering is carried out for 8 hours; the heating time is 2000°C for 9 hours; and the temperature is kept at 2300°C for 5 hours. After high-temperature purification sintering, the silicon carbide boat support split component blank is obtained.
[0041] The high-temperature siliconization sintering adopts a vacuum graphite electrode furnace. Before heating, the vacuum is first evacuated to a vacuum degree of less than 5Pa, and heating is started. The temperature is 200℃ for 2 hours, and vacuum is evacuated; the temperature is 900℃ for 6 hours, and vacuum is stopped. High-purity nitrogen is filled to restore normal pressure, and the wax exhaust fan is started to remove organic matter, and high-purity nitrogen is continuously filled at a rate of 100ml / min; heating at 1100℃ for 2 hours, vacuum is evacuated; heating at 1300℃ for 3 hours; heating at 1500℃ for 4 hours; heating at 1650℃ for 4 hours; and keeping at 1650℃ for 2 hours. High-purity nitrogen is filled when cooling down, and the temperature is naturally cooled down.
[0042] Preparation Example 1
[0043] The preparation method of the dispersant comprises the following steps:
[0044] S1. 100 g of graphene oxide, 50 g of 2-acrylamide-2-methylpropanesulfonic acid, 25 g of N,N-methylenebisacrylamide, 15 g of diethylenetriamine, 35 g of methylcellulose, and 20 g of polyethylene glycol were mixed uniformly and allowed to stand at 50° C. for 30 min to obtain a primary mixture;
[0045] S2. Add the primary mixture into a vacuum homogenizer for vacuum homogenization, control the vacuum degree during vacuum homogenization to be 0.1Mpa, the speed to be 1500rpm, and the homogenization time to be 30min;
[0046] S3. After homogenization, vacuum spray drying is performed, and the vacuum degree is controlled to be 0.3MPa, the atomization pressure is 0.5MPa, the inlet air temperature is 110°C, and the outlet air temperature is 45°C. After spray drying, the modified dispersant is obtained.
[0047] Preparation Example 2
[0048] The preparation method of the dispersant comprises the following steps:
[0049] S1. 100 g of graphene oxide, 50 g of 2-acrylamide-2-methylpropanesulfonic acid, 25 g of N,N-methylenebisacrylamide, 15 g of diethylenetriamine, 35 g of methylcellulose, and 20 g of polyethylene glycol were mixed uniformly and allowed to stand at 55° C. for 35 min to obtain a primary mixture;
[0050] S2. Add the primary mixture into a vacuum homogenizer for vacuum homogenization, control the vacuum degree during vacuum homogenization to be 0.2Mpa, the speed to be 1800rpm, and the homogenization time to be 45min;
[0051] S3. After homogenization, vacuum spray drying is performed, and the vacuum degree is controlled to be 0.4MPa, the atomization pressure is 0.7MPa, the air inlet temperature is 112°C, and the air outlet temperature is 50°C. After spray drying, the modified dispersant is obtained.
[0052] Preparation Example 3
[0053] The preparation method of the dispersant comprises the following steps:
[0054] S1. 100 g of graphene oxide, 50 g of 2-acrylamide-2-methylpropanesulfonic acid, 25 g of N,N-methylenebisacrylamide, 15 g of diethylenetriamine, 35 g of methylcellulose, and 20 g of polyethylene glycol were mixed uniformly and allowed to stand at 60° C. for 40 min to obtain a primary mixture;
[0055] S2. Add the primary mixture into a vacuum homogenizer for vacuum homogenization, control the vacuum degree during vacuum homogenization to be 0.3Mpa, the speed to be 2000rpm, and the homogenization time to be 60min;
[0056] S3. After homogenization, vacuum spray drying is performed, and the vacuum degree is controlled to be 0.5MPa, the atomization pressure is 0.8MPa, the inlet air temperature is 115°C, and the outlet air temperature is 55°C. After spray drying, the modified dispersant is obtained.
[0057] Example 1
[0058] A method for manufacturing a boat support comprises the following steps:
[0059] S1. 160 g of raw material, 6 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and dried with hot air to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0060] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0061] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 90 μm, 8 μm and 1.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (30:15:47):2;
[0062] The organic auxiliary agent is a mixture of the binder OPTAPIXAC112, the modified dispersant prepared in Preparation Example 1, and the defoamer CONTRASPUM KWE in a mass ratio of 3:6:1;
[0063] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0064] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas to obtain a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0065] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0066] Example 2
[0067] A method for manufacturing a boat support comprises the following steps:
[0068] S1. 160 g of raw material, 6 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and dried with hot air to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0069] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0070] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 95 μm, 9 μm and 2 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (32:18:48):2.5;
[0071] The organic auxiliary agent is a mixture of binder OPTAPIXAC112, the modified dispersant prepared in Preparation Example 2, and defoamer CONTRASPUM KWE in a mass ratio of 3:6:1;
[0072] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0073] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0074] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0075] Example 3
[0076] A method for manufacturing a boat support comprises the following steps:
[0077] S1. 160 g of raw material, 6 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and dried with hot air to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0078] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0079] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 100 μm, 10 μm and 2.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (35:20:50):3;
[0080] The organic auxiliary agent is a mixture of the binder OPTAPIXAC112, the modified dispersant prepared in Preparation Example 1, and the defoamer CONTRASPUM KWE in a mass ratio of 3:6:1;
[0081] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0082] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0083] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0084] Example 4
[0085] A method for manufacturing a boat support comprises the following steps:
[0086] S1. 165 g of raw material, 7 g of organic additive and 4 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0087] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0088] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 90 μm, 8 μm and 1.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (32:16:48):2.5;
[0089] The organic auxiliary agent is a mixture of the binder OPTAPIXAC112, the modified dispersant prepared in Preparation Example 1, and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;
[0090] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0091] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0092] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0093] Example 5
[0094] A method for manufacturing a boat support comprises the following steps:
[0095] S1. 165 g of raw material, 7 g of organic additive and 4 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0096] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0097] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 95 μm, 9 μm and 2 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (32:18:49):2.5;
[0098] The organic auxiliary agent is a mixture of binder OPTAPIXAC112, modified dispersant prepared in Preparation Example 2 and defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;
[0099] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0100] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0101] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0102] Example 6
[0103] A method for manufacturing a boat support comprises the following steps:
[0104] S1. 165 g of raw material, 7 g of organic additive and 4 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0105] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0106] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 100 μm, 10 μm and 2.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (35:20:50):3;
[0107] The organic auxiliary agent is a mixture of the binder OPTAPIXAC112, the modified dispersant prepared in Preparation Example 3, and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;
[0108] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0109] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0110] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0111] Example 7
[0112] A method for manufacturing a boat support comprises the following steps:
[0113] S1. 170 g of raw material, 8 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0114] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0115] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 90 μm, 8 μm and 1.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (30:15:47):2;
[0116] The organic auxiliary agent is a mixture of the binder OPTAPIXAC112, the modified dispersant prepared in Preparation Example 1, and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;
[0117] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0118] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0119] S3. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0120] Example 8
[0121] A method for manufacturing a boat support comprises the following steps:
[0122] S1. 170 g of raw material, 8 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0123] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0124] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 95 μm, 9 μm and 2 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (33:18:49):2.5;
[0125] The organic auxiliary agent is a mixture of binder OPTAPIXAC112, modified dispersant prepared in Preparation Example 2 and defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;
[0126] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0127] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0128] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0129] Example 9
[0130] A method for manufacturing a boat support comprises the following steps:
[0131] S1. 170 g of raw material, 8 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;
[0132] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;
[0133] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 100 μm, 10 μm and 2.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (35:20:50):3;
[0134] The organic auxiliary agent is a mixture of the binder OPTAPIXAC112, the modified dispersant prepared in Preparation Example 3, and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;
[0135] S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50min, and completing the ozone treatment to obtain the modified semi-finished product;
[0136] S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;
[0137] S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1700°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.
[0138] Comparative Example 1
[0139] The difference between this comparative example and Example 1 is that the dispersant prepared in Preparation Example 1 is replaced by a common commercially available PRODUKT KV 5088 dispersant.
[0140] Comparative Example 2
[0141] The difference between this comparative example and Example 1 is that the dispersant prepared in Preparation Example 1 is replaced by common commercially available methyl cellulose purchased from Hubei Kewode Chemical Co., Ltd. with a CAS number of 9004-67-5.
[0142] Comparative Example 3
[0143] The difference between this comparative example and Example 1 is that the dispersant prepared in Preparation Example 1 is replaced by common commercially available polyethylene glycol purchased from Jinan Yuanlian Chemical Co., Ltd. with a CAS number of 25322-68-3.
[0144] Comparative Example 4
[0145] The difference between this comparative example and Example 1 is that the raw materials are common commercially available green silicon carbide powder and ultrapure carbon black;
[0146] Green silicon carbide powder was purchased from Dongguan Zhuofeng Surface Treatment Materials Co., Ltd., model number 240; ultra-pure carbon black was purchased from Shanghai Kaiyin Chemical Co., Ltd., item number AC80.
[0147] The samples prepared in Examples 1-9 and Comparative Examples 1-4 were tested; the specific experimental data are shown in Table 1:
[0148] Take a sample of 25×25×125mm and use the three-point bending method and an automatic bending tester to test the bending strength of the sample at 1100℃;
[0149] Thermal conductivity adopts GB / T22588-2008 flash method to measure thermal diffusivity or thermal conductivity;
[0150] The porosity adopts the GB / T1966-1996 porous ceramic apparent porosity and capacity test method;
[0151] Wear resistance test: refer to GB / T9867-2008.
[0152] Table 1
[0153]
[0154]
[0155] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for manufacturing a boat support, characterized in that: The following steps are involved: S1. Prepare slurry by mixing raw materials, organic additives and pure water in a ball mill according to a certain proportion, and obtain a blank of the boat support split component by a slip injection molding process. After the blank is naturally dried and dried with hot air to remove moisture, it is trimmed and carved into a semi-finished boat support split component that meets the size requirements; The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal; The organic additive is a mixture of a binder, a dispersant and a defoamer; S2, using a UV lamp to treat the semi-finished product with ozone, controlling the emission wavelength of the UV lamp to be 185nm, and the irradiation time of the UV lamp to be 50-60min, and completing the ozone treatment to obtain a modified semi-finished product; S3, putting the modified semi-finished product described in S2 into an induction furnace, and sintering it at a temperature of 2000-2300° C. under the protection of inert gas, and obtaining a green blank of the silicon carbide boat support splitting component after high-temperature purification and sintering; S4. The split blanks of the silicon carbide boat support are spliced together. After being spliced into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650-1700℃. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning and drying processes to obtain a boat support with low iron content.
2. The method for manufacturing a boat support according to claim 1, characterized in that: The mass ratio of the raw material, the organic auxiliary agent and the pure water is (160-170):(6-8):(3-5).
3. The method for manufacturing a boat support according to claim 1, characterized in that: The green silicon carbide powder is mixed with green silicon carbide powder having three particle size distributions of average particle size of 90 to 100 μm, 8 to 10 μm and 1.5 to 2.5 μm; The mass ratios of green silicon carbide powder with three particle size distributions to ultrapure carbon black are controlled within the range of [(30-35):(15-20):(47-50)]:(2-3).
4. The method for manufacturing a boat support according to claim 1, characterized in that: The method for high-temperature impurity removal treatment of the ultra-pure carbon black is as follows: commercially available carbon black with a purity of ≥99% is sent into a vacuum furnace, and subjected to high-temperature impurity removal treatment at 1600 degrees in a vacuum state to obtain ultra-pure carbon black with a purity of ≥99.9%.
5. The method for manufacturing a boat support according to claim 1, characterized in that: The silicon used in the high-temperature siliconizing and sintering treatment is semiconductor silicon with a purity of 99.99% and a particle size of 3 to 5 mm. After the surface coating treatment, the semiconductor silicon is roasted together with the boat support that needs siliconizing treatment in a weight ratio of 15 to 30:
100. The surface coating treatment is to add a slurry of ultra-pure carbon black, hexagonal boron nitride, PVP K90 and water during the heating and stirring of the semiconductor silicon, so that a layer of coating is coated on the surface of the silicon particles, a certain amount of moisture is quickly removed, and then it is slowly dried. Before being put into the kiln, it is forced to be dried at 80°C again to ensure that there is no moisture and the surface coating is intact.
6. The method for manufacturing a boat support according to claim 1, characterized in that: The impurity removal process uses dilute hydrochloric acid, the concentration of which is controlled at 8-15%, the temperature at 20-40° C., and the soaking time at 20-60 minutes.
7. The method for manufacturing a boat support according to claim 1, characterized in that: The organic auxiliary agents are a binder, a dispersant and a defoamer, which are mixed in a mass ratio of (3-5): (6-8): (1-2).
8. The method for manufacturing a boat support according to claim 7, characterized in that: The adhesive is OPTAPIXAC112; The defoamer is CONTRASPUM KWE.
9. The method for manufacturing a boat support according to claim 1, characterized in that: The preparation method of the dispersant comprises the following steps: S1. Mix graphene oxide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, diethylenetriamine, methylcellulose and polyethylene glycol uniformly and stand at 50-60° C. for 30-40 minutes to obtain a primary mixture; S2. Add the primary mixture into a vacuum homogenizer for vacuum homogenization, control the vacuum degree during vacuum homogenization to be 0.1-0.3Mpa, the rotation speed to be 1500-2000rpm, and the homogenization time to be 30-60min; S3. After homogenization, vacuum spray drying is performed, and the vacuum degree is controlled to be 0.3-0.5MPa, the atomization pressure is 0.5-0.8MPa, the air inlet temperature is 110-115°C, and the air outlet temperature is 45-55°C. After spray drying, the modified dispersant is obtained.
10. A boat support manufactured according to the manufacturing method according to any one of claims 1-9.
Citation Information
Patent Citations
High-thermal-conductivity pressurelessly-sintered silicon carbide ceramic material and preparation method thereof
CN104926312A
Charging method of reaction sintered silicon carbide
CN108706977A
Preparation method of reaction sintering silicon carbide large boat support
CN113880582A
Process for sintering silicon carbide ceramic through gel casting reaction
CN114560703A
Manufacturing method of low-iron-content pollution-free silicon carbide boat support for photovoltaics and semiconductors
CN118894726A
Cited By
Preparation method of high-purity silicon carbide tile boat
CN120817808A
A method for preparing high-purity silicon carbide tile boats
CN120817808B